Middle East respiratory coronavirus (MERS-CoV) spike (S) protein vesicular stomatitis virus pseudoparticle neutralization assays offer a reliable alternative to the conventional neutralization assay in human seroepidemiological studies. Issue 9 (11th November 2019) - Lester, Sandra; Harcourt, Jennifer; Whitt, Michael; Al-Abdely, Hail M.; Midgley, Claire M.; Alkhamis, Abdulrahim M.; Aziz Jokhdar, Hani A.; Assiri, Abdullah M.; Tamin, Azaibi; Thornburg, Natalie
Abstract : Middle East respiratory syndrome coronavirus (MERS-CoV) is a novel zoonotic coronavirus that was identified in 2012. MERS-CoV infection in humans can result in an acute, severe respiratory disease and in some cases multi-organ failure; the global mortality rate is approximately 35 %. The MERS-CoV spike (S) protein is a major target for neutralizing antibodies in infected patients. The MERS-CoV microneutralization test (MNt) is the gold standard method for demonstrating prior infection. However, this method requires the use of live MERS-CoV in biosafety level 3 (BSL-3) containment. The present work describes the generation and validation of S protein-bearing vesicular stomatitis virus (VSV) pseudotype particles (VSV-MERS-CoV-S) in which the VSV glycoprotein G gene has been replaced by the luciferase reporter gene, followed by the establishment of a pseudoparticle-based neutralization test to detect MERS-CoV neutralizing antibodies under BSL-2 conditions. Using a panel of human sera from confirmed MERS-CoV patients, the VSV-MERS-CoV particle neutralization assay produced results that were highly comparable to those of the microneutralization test using live MERS-CoV. The results suggest that the VSV-MERS-CoV-S pseudotype neutralization assay offers a highly specific, sensitive and safer alternative method to detect MERS-CoV neutralizing antibodies in human sera.